Micro-Computed Tomographic Evaluation of Sealing Ability of Different Bioceramic Endodontic Sealers: An in vitro Study - Saya H. Raouf; Dara H. Saeed (Polytechnic Journal)
The aim of the present study was to compare sealing ability of three bioceramic sealers, including Endosequence BC and BioRoot RCS, with bioceramic-coated gutta-percha cone (BCGP) or GP in comparison to a clinical reference standard AH Plus sealer using high-resolution micro-computed tomography (micro-CT) analysis. Fifty freshly extracted single canal premolars were included in the study. All the samples were prepared using 2 Shape rotary system TS1 (25/0.04), TS2 (25/0.06), and F35 (35/0.06) file. After completion of the instrumentation, the samples were randomly divided based on the sealer material used and GP into four experimental groups and one control group with Endosequence, BioRoot, and AH Plus sealers with BCGP and conventional GP. All groups were obturated with (35/0.06) single cone obturation and high resolution of micro-CT was used to determine percentage of voids within the canals. BCGP showed better result than GP at all groups. In BCGP group, there were no significant differences in the percentage of the voids except internal voids. However, in all conventional GP groups, there were significant differences. Within the limitations of this study, it could be concluded that none of the groups were free of voids, BCGP with bioceramic sealer significantly better than GP.